Perlindungan Hukum Pasien CoAss di Rumah Sakit Gigi dan Mulut Pendidikan - Kurniawan, Hansen; Chomariyah; Nugraheni, Ninis (Magister Ilmu Hukum - Universitas Hang Tuah, 2025)
The public always asks whether the rights obtained by patients while being treated by dentists compared to CoAss dentists are the same and whether they get legal protection while being treated by CoAss dentists. This research aims to discuss the legal protection of patients who are treated by CoAss dentists at the Dental Education Hospital. The method used in this study is a normative legal methodology and descriptive analytical with an approach to Law no. 17 of 2023 concerning Health (Health Law). The results of the study show that patients have the right to fulfill their rights, including obtaining complete information, consent to medical actions, confidentiality, and legal protection from negligent acts regulated in the Health Law and PP 28 of 2024 concerning implementing regulations for the Health Law.. patient rights and legal responsibilities towards CoAss operating under the supervision of senior doctors/DPJP can be fulfilled. The findings show that even though CoAss doesn’t yet have a practice permit, patient rights at RSGMP are still fulfilled, with procedures that prioritize patient safety. This article emphasizes the importance of strict supervision from institutions,clear regulations regarding patient rights, and the need for a complaint mechanism to improve the quality of medical services.